Modelo de avaliação de desempenho de operação e manutenção de usinas fotovoltaicas de minigeração distribuída - Rediske, Graciele (2023)
With the increasing demand for electrical energy, it is important that power generation plants are managed efficiently and economically. Among the options for generating electricity, one of the fastest growing worldwide is generation using photovoltaic (PV) technology. Based on a careful evaluation of the performance of the PV plants, it is observed that there is an opportunity for improvement through the indirect addition of capacity. This process consists of reducing as much as possible the losses that can be mitigated through adequate operation and maintenance (O&M) strategies. As PV plants age, the need for efficient monitoring of O&M increases, helping to understand the situation of the plant, identifying problems and proposing solutions for the formation of future strategies. The objective of this study is to use a performance evaluation method built on a mathematical model capable of measuring the O&M performance level of PV plants, classified as distributed mini-generation, with installed power between 75 kW and 5 MW. A set of key performance indicators (KPIs) was established through the systematic literature review (SLR) methodology, associated with the Delphi method, and allocated into three categories: Energy Performance, O&M Services and Operational Finance. Mathematical modeling proposed the use of the SWARA method to differentiate the level of importance and complexity of measuring KPIs under the judgment of industry experts. By obtaining this information, an effort and impact matrix was constructed, contemplating the proposed set of KPIs. The study presents a comprehensive set of 30 KPIs capable of quantitatively measuring the O&M performance of a PV plant. The results show that the KPIs "Performance rate" and "Availability of spare parts" are the most important in this evaluation, and that the KPI "Contractual availability" presents greater complexity in measuring its parameters. By viewing the impact effort matrix, it is possible to verify that the KPI “compliance rate with the preventive maintenance schedule” stands out compared to the others, presenting a high level of importance and low level of complexity in its measurement. The design of the formulation for measuring performance relates a KPI to the fulfillment of the established goal, in order to verify the performance of the plant in that aspect. The information resulting from this work seeks to help PV plant managers to select the appropriate KPIs to measure the status of the PV plant's O&M management.